Influence Openness to Experience, Conscientiousness, Extraversion, Agreeableness, Neuroticism on Performance with Self-Efficacy as Mediator - Puspita Dewi, Nolla; Satriawan, Bambang; Yanti, Sri; Faizah, Ana; Nurhatisyah; Wibisono, Chablullah; Khaddafi, Muamar; Tohara (International Journal of Psychosocial Rehabilitation, 2020)
Micro, small, and medium enterprises (SMEs) have a crucial role in the commercial growth of a country. Some researchers suggest that the inability of SMEs to improve competitiveness is caused by the SMEs that have various limitations, such as lack of ability to adapt to the environment, lack of agility in business opportunities, and lack of creativity and innovation in anticipation of a variety of environmental challenges in the industry. 4.0 revolution era. The population in this survey at the Department of Cooperatives and SMEs in Batam, the number of samples used in this study after calculation by the formula Slovin, is 150. The data were analyzed using a structural equation model. The software used for the structural analysis is AMOS and SPSS for descriptive studies. Research shows that: Extroversion on performance through self-efficacy had a significant effect, Agreeableness on performance through self-efficacy has a significant impact, Neuroticism on performance through self-efficacy has a significant effect. From the results of this study, it is suggested that the government support the findings of research outcome variables that will be done and SMEs prepare for the evolution of Indonesian SMEs towards digital marketing.